ChemInform Abstract: Direct CuO Nanoparticle‐Catalyzed Synthesis of Poly‐Substituted Furans via Oxidative C—H/C—H Functionalization in Aqueous Medium. Issue 34 (4th August 2016) - Payra, Soumen; Saha, Arijit; Guchhait, Sandip; Banerjee, Subhash
Abstract: The title furans are prepared by functionalization of 1, 3‐dicarbonyls or β‐keto esters with α, β‐unsaturated carbonyl compounds via conjugate addition initiated domino reaction.